PENINGKATAN NILAI TAMBAH DALAM PEMANFAATAN TONGKOL JAGUNG SEBAGAI ALTERNATIF PAKAN TERNAK BAGI KELOMPOK TANI GEMA BAKTI RAYA - R, St Aisyah; Djunu, Sri Suryaningsih; Apriliani, Silvana; Mada, Andika; Taja, Jikran; Karim, Arjuna Andika Putra (Jurnal Abdi Insani, 2024)
Corn cob waste is a residue of agricultural production that has the potential as an alternative animal feed, but the waste has not been maximally utilized by farmers who are members of the Gema Bakti Raya Farmer Group. Corn cobs, which have been discarded or burned after shelling, have great potential that has not been utilized by farmer groups, which can cause environmental problems and accumulation of waste if left unattended. On the other hand, during the dry season there is a scarcity of animal feed and corn cobs can be an effective solution by utilizing appropriate technology as an alternative to ruminant feed with the fermentation method. The purpose of this PKM is to motivate and increase community awareness of corn waste handling and increase partners' knowledge and skills in utilizing corn cobs as an alternative animal feed. The several stages of this activity include: socialization, counseling and training, technology application, mentoring and evaluation and sustainability.  The results of the service implementation show that the transfer of knowledge, skills and technology, especially appropriate technology (TGG) to partner groups has increased partner knowledge by 50% and increased partner skills by 60%.   The PKM program can empower partner groups to access their potential.  This is expected to provide economic and environmentally friendly added value and have an impact on increasing income and sustainability of corn farming.